Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - Review Exercises - Page 63: 56


$-\frac{3}{\sqrt 2+\sqrt {11}}$

Work Step by Step

$\frac{\sqrt 2-\sqrt {11}}{3}=\frac{\sqrt 2-\sqrt {11}}{3}\frac{\sqrt 2+\sqrt {11}}{\sqrt 2+\sqrt {11}}=\frac{\sqrt 2(\sqrt 2)+\sqrt 2(\sqrt {11})-\sqrt {11}(\sqrt 2)-\sqrt {11}(\sqrt {11})}{3(\sqrt 2+\sqrt {11})}=\frac{(\sqrt 2)^2-(\sqrt {11})^2}{3(\sqrt 2+\sqrt {11})}=\frac{2-11}{3(\sqrt 2+\sqrt {11})}=\frac{-3(3)}{3(\sqrt 2+\sqrt {11})}=\frac{-3}{\sqrt 2+\sqrt {11}}=-\frac{3}{\sqrt 2+\sqrt {11}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.